On whiteness the Racial Imaginary Institute - Alcoff, Linda 1955-; Bell, Alexandra 1983-; Berlant, Lauren Gail 1957-2021; Bery, Sadhana; Borzutzky, Daniel 1974-; Caflisch, Jane; Chang, Jeff; Chin, Mel 1951-; D'Souza, Aruna 1969-; Gonzales-Day, Ken 1964-; Gruen, Lori 1962-; Hartman, Saidiya V. 1961-; et al. (SPBH Editions, 2022)
"Cofounded in 2017 by authors Claudia Rankine and Beth Loffreda, the Racial Imaginary Institute (TRII) is an interdisciplinary collective of artists, writers, knowledge-producers and activists. The institute's historic 2018 symposium 'On Whiteness' convened a dazzling array of thinkers, artists and activists. The essays that resulted from the event, collected here, seek to examine whiteness as a source of often unquestioned or even unobserved power, and make visible variations of this dangerous ideology that has been intentionally positioned as neutral. In our current moment, whiteness is freshly articulated: as a source of unquestioned power, and as a 'bloc', it feels itself endangered even as it retains its hold on power. Given that the concept of racial hierarchy is a strategy employed to support white dominance, whiteness is an important aspect of any conversation about race. The essays in On Whiteness make visible what has been intentionally presented as inevitable to help the move forward into more revelatory conversations about race. They question what can be made when we investigate, evade, beset and call out 'bloc whiteness.'"--
Papers from a symposium co-organized by The Racial Imaginary Institute and The Kitchen, held at The Kitchen in Manhattan, June 30, 2018
Keywords: Weißsein; White people / Race identity / Congresses; White privilege (Social structure) / Congresses; Race in art / Exhibitions; Race in art; White people / Race identity; White privilege (Social structure); Exhibition catalogs; Conference papers and proceedings; Konferenzschrift -- 2018